The screening effects of the screened exchange hybrid functional in surface systems: A case study on the CO/Pt(111) problem - Roland Gillen (AIP Advances, 2016)
The screened exchange (sX) hybrid functional has been widely used in computational material science. Although it has widely been studied in bulk systems, less is known about its functional behavior in surface systems which are crucial to many technologies such as materials synthesis and nano-electronic devices. Assessing the screening dependent functional behaviors in the surface systems is therefore important for its application in such systems. In this work, we investigate the screening effects of the sX in CO adsorption on Pt(111) surface. The differences between the sX and Heyd-Scuseria-Ernzerhof (HSE06) hybrid functionals, and the effects of screening parameters are studied. The screening has two effects: first, the HOMO-LUMO gap is screening dependent. This affects the site preference most significantly. In this work, atop adsorption of CO/Pt(111) is predicted by the hybrid functionals with screened exchange potential. The sX(1.44) gives the largest HOMO-LUMO gap for the isolated CO molecule. The adsorption energy difference between the atop and fcc site is also the largest by the sX(1.44) which is explained by the reduced metal d states to the CO 2π* state back-donation, with stronger effect for the fcc adsorption than for the atop adsorption; second, the adsorption energy is screening dependent. This can be seen by comparing the sX(2.38) and HSE06 which have different screening strengths. They show similar surface band structures for the CO adsorption but different adsorption energies, which is explained by the stronger CO 5σ state to the metal d states donation or the effectively screened Pauli repulsion. This work underlines the screening strength as a main difference between sX and HSE06, as well as an important hybrid functional parameter for surface calculation.